Attributes of Low Back pain among Physical Therapists and Nurses in Pakistan : Low Back Pain among Physical Therapists and Nurses - Badar, Shahid; Abro, Sara Aamir; Zaman, Bushra Marium; Zia, Kashmala; Arzoo, Obaida; Sandeela, Khadijatul Ain; Peer Muhammad, Madiha; Ansari, Komal (Pakistan Journal of Health Sciences, 2024)
Low back pain is localized between the region of the 12th rib and less to the gluteal folds either radiating or not radiating to the lower limb. The prevalence of low back pain in Pakistan is about 41.4 percent. But all over the world, the Physical therapist’s rate of work-related musculoskeletal problems is about 57 percent. Objective: To determine the attributes of low back pain among physical therapists and nurses in Pakistan. Methods: A cross-sectional study was done from August 2023 to January 2024, throughout Pakistan. A sample size of 661 was divided into two groups. The sampling technique was non-probability purposive sampling. There were two measurement tools used Visual Analog Scale and the Oswestry Disability Index scale to rule out pain and the level of disability. The data were analyzed through SPSS version 23.0 software. Results: The total number of participants was 661, of which 247 were physical therapists and 414 were nurses recruited from all over Pakistan. The pain was measured through the VAS and disability was measured by ODI. The Physical therapists felt mild pain in about 123(49.79%), and they faced no disability in about 127(51.41%) and nurses felt moderate pain in about 212(51.20%) and they have not faced disability in about 306(73.91%). Conclusions: Our study concluded the prevalence of low back pain is found in both nurses and physical therapists but the level of pain is higher in nurses as compared to a physical therapist due to the lack of ergonomics knowledge among the nurse population.